Role of routine chest xrays and device checks in detecting peri-procedural complications associated with cardiac device implantation: a UK tertiary centre experience. (3rd October 2022) - Menexi, C; Elrefai, M; Chua, A Y T; Handa, I; Abouelasaad, M; Paisey, J
Abstract: Introduction: Complications associated with Cardiac implantable electronic devices (CIEDs) are not uncommon, most of which occur in the perioperative phase. Until recently, guidance on implemented measures for early detection of peri-operative complications were lacking. The ESC guidelines on pacing recommend routine follow up of all newly implanted devices within 72 hours of implant. While the recently published EHRA expert consensus and practical guide on CIEDs recommend that a chest x-ray should be performed within 24 hours in all patients to rule out pneumothorax and document lead positions. Purpose: At our tertiary centre for CIEDs, it is routine practice to perform CIEDs implantations on a day-case basis, targeting same day discharge for uncomplicated procedures. CXRs are performed 4 hours after the implant, and CIEDs are fully checked twice, once "on table" at the end of the procedure, and again after mobilisation and prior to discharge. In our analysis, we aimed to identify the yield of complications that could be detected early-on using these routine measures in all our implant procedures. Methods: We performed a retrospective analysis of consecutive CIED implants performed between January and December 2019. The following information were collected; types and indications for device therapy, device checks reports, CXR reports, and clinical notes for documented symptoms or signs suggestive of peri-procedural complications. Results: A total of 578 patients (Age 74±16 years, 68% male) were included in our analysis, for demographics see table. All patients had routine CXRs and 2 device checks. There were 16 (2.8%) peri-procedural complications associated with our device implants, 7 (1.2%) pneumothoraxes, 6 (1%) pericardial effusions, and 3 (0.5%) lead displacements. In 4 out of the 7 peri-procedural pneumothoraxes, the operator reported difficulty gaining access. 2 patients with pneumothorax reported chest pain, 1 patient reported shortness of breath and 1 had low O2 saturations. There were 2 asymptomatic cases of pneumothorax after reportedly straightforward procedures and were only detected on the routine CXRs, one of them required chest drain insertion and the other treated conservatively. 2 out of the 3 lead displacements were detected on both CXRs and pre-discharge pacing checks and didn't require intervention, while 1 case of lead displacement occurred after the pacing checks and CXRs were reported to be satisfactory, further pacing checks triggered by patient's symptoms and bradycardia on the monitor revealed lead displacement requiring intervention prior to discharge. Conclusion: Routine post CIED implantation CXRs can detect early – otherwise clinically silent-periprocedural complications and appropriately remains a requirement for all CIED implants. While repeat post mobilisation device checks has low yield of detection of complications and can be reasonably abandoned provided that initial "on-table" checks are satisfactory. Funding Acknowledgement: Type of funding sources: None.